TEXTILE PRINTING DESIGN APPLICATIONS: ORIGINAL DESIGNS BY INSPIRING WORKS OF TURKISH ISLAMIC CIVILIZATION - Mehmet Zahit BİLİR (Fırat University, 2019)
Informations and works from history have been tried to delivered to people via science disciplines such as history and archaeology etc. There are some education ways using materials and kits in daily life to transfer history correctly and continuously in addition to digital broadcast. Turkish Islamic works have wide wealth in terms of high number of works and fine art works requiring mastery. One of these applications that can collect Turkish Islamic works and people together and can help understanding these wealthes more is textile printing design application. Printing process is one of applications to make textile products ready for use. Printing process that is coloring of textile surfaces with various metods has been applied continuously from the oldest periods of history to 21. century that tecthnology have made pick. One of printing methods is serigraphy (silk) method and this method is applied often today. More than one color can be printed on textile surfaces at high quality with serigraphy printing tecnique. In this study, motifs and architectural features in some mosques and madrasah built in Turk Islamic Civilization time have been analyzed and then various patterns have been designed by inspiring from this motif and architectural structures by using Adobe Illustrator programme and have applied on textile surfaces. Created patterns to apply serigraphy technique have been printed on textile surfaces with silk stretching, emulsfying, drying, washing, printing and then fixing processes. In the result of this study, informing about serigraphy printing method application, showing features of works from Turkish Islamic civilization, showing that original designs can be made by inspiring from Turkish Islamic works in textile printing design and providing more people to have more informations about Turkish Islamic civilization works with these created products have been targeted